2019
DOI: 10.1038/s41586-019-1452-4
|View full text |Cite
|
Sign up to set email alerts
|

A dominant population of optically invisible massive galaxies in the early Universe

Abstract: Our current knowledge of cosmic star-formation history during the first two billion years (corresponding to redshift z > 3) is mainly based on galaxies identified in rest-frame ultraviolet light 1 . However, this population of galaxies is known to under-represent the most massive galaxies, which have rich dust content and/or old stellar populations. This raises the questions of the true abundance of massive galaxies and the star-formation-rate density in the early universe. Although several massive galaxies th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
318
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(355 citation statements)
references
References 79 publications
33
318
4
Order By: Relevance
“…While such massive high-redshift DSFGs are rare, their existence implies that other galaxies as massive as XMM-2599 at z ∼ 3.5 exist. Moreover, though many of these DSFGs have clear optical counterparts, the recent discovery of a significant number of DSFGs at 3 < z < 8 with no such counterpart indicates that such galaxies may exist in sufficient numbers to be progenitors of the z > 3 quiescent UMG population down to even lower masses, and have simply avoided detection thus far (Williams et al 2019;Wang et al 2019).…”
Section: Progenitors Of Quiescent Umgsmentioning
confidence: 99%
See 1 more Smart Citation
“…While such massive high-redshift DSFGs are rare, their existence implies that other galaxies as massive as XMM-2599 at z ∼ 3.5 exist. Moreover, though many of these DSFGs have clear optical counterparts, the recent discovery of a significant number of DSFGs at 3 < z < 8 with no such counterpart indicates that such galaxies may exist in sufficient numbers to be progenitors of the z > 3 quiescent UMG population down to even lower masses, and have simply avoided detection thus far (Williams et al 2019;Wang et al 2019).…”
Section: Progenitors Of Quiescent Umgsmentioning
confidence: 99%
“…Over the last decade, deeper and wider field nearinfrared detected multi-wavelength surveys have enabled the discovery and photometric investigation of rare ultra-massive galaxies (UMGs; M * > 10 11 M ) at progressively higher redshifts (e.g., Rodighiero et al 2007;Wiklind et al 2008;Mancini et al 2009;Marchesini et al 2010;Stefanon et al 2015;Marsan et al 2017). Although most UMGs observed at z > 2 are still forming stars, often quite vigorously (Martis et al 2016;Whitaker et al 2017;Wang et al 2019;Martis et al 2019), the number of quiescent candidates has been increasing and exceeds the predictions of simulations by a factor of between 3 and 30, depending upon selection criteria (e.g., Straatman et al 2014;Guarnieri et al 2019;Alcalde Pampliega et al 2019). A handful of these massive quiescent systems have been spectroscopically confirmed at 1.5 < z < 2.5, enabling a more precise characterization of their stellar populations, and improved modeling of their star formation histories due to the de-tection of stellar continuum features (e.g., Kriek et al 2016;Kado-Fong et al 2017;Belli et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…-One example pertains to early stages of galaxies that are not visible at visible light wavelengths. (See reference [52].) Observations feature sub-millimeter wavelength light.…”
Section: Galaxies Components Of Galaxies and Ratios Of Dark Matter mentioning
confidence: 99%
“…The model shows mainly early formation of galaxies, which is not usually considered, although recent observations have shown that organized strucutures did exist as early as 400 [My]. Recently, Wang et al (2019) have observed the existence of 39 massive and mature galaxies only 2 [ ] after the beginnings of the universe. However, the mass accumulation model (radius growth) is very basic, and a fullcapacity accumulation model based on existing forces would be more realistic and would surely yield more accurate galactic growth rates.…”
Section: Summary Of the Galaxy Rotation Modelmentioning
confidence: 99%